PERAN FILOSOFI PENDIDIKAN DALAM MEMBENTUK GURU REFLEKTIF DAN HUMANIS PADA PROGRAM PENDIDIKAN PROFESI GURU: KAJIAN KEPUSTAKAAN - Nyoman Astawan; I Nyoman Sadwika; I Ketut Muada (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
ABSTRACT Educational philosophy plays a strategic role in the formation of professional teachers, particularly within the context of the Teacher Professional Education Program (Program Pendidikan Profesi Guru PPG), which has tended to emphasize technical and instructional aspects. This article aims to conceptually examine the role of educational philosophy as a foundational framework for developing reflective and humanistic teachers in PPG. The study employs a qualitative approach using a literature review method through the analysis of reputable scholarly books, peer-reviewed journal articles, and relevant educational policy documents. The findings indicate that educational philosophy functions as a value-based framework that shapes the orientation and objectives of teacher education and has direct implications for the selection and design of learning models in PPG. The integration of educational philosophical traditions such as idealism, progressivism, humanism, constructivism, and critical philosophy strengthens reflective, humanistic, and contextual learning approaches oriented toward ethical and humanistic values. The conceptual synthesis of this study underscores that strengthening educational philosophy should be positioned as an integrative foundation in PPG, ensuring that the development of professional teachers is not reduced to technical skills training but becomes a reflective, humanistic, and value-oriented educational process